Alignment Efficiency of Two Archwires in Adolescents with Moderate to Severe Crowding - Sáenz, Ivette (Odovtos - International Journal of Dental Sciences, 2024)
There is no consensus in clinical orthodontics on which aligning arch wire should be used at the initial stage of treatment. This randomized clinical trial evaluated the efficiency of multistranded Nitinol (Supercable) aligning arch-wire versus a standard arch-wire (Nitinol) in the first stage of orthodontic treatment in adolescents with severe crowding. Forty patients ages 12 to 17 with an Irregularity Index as proposed by Little between 5 to 17 mm were selected. Vinyl polysiloxane impressions (VPS) were taken before treatment (T1) at 6 weeks (T2) and 12 weeks (T3). Roth prescription .022 x .028 Edgewise brackets were bonded using light cure adhesive to the six anterior teeth of each dental arch and bands were placed on all first molars. Subjects were paired by gender and Irregularity Index into two groups of 20 each and assigned either to the control group (Nitinol) or the experimental archwire (Supercable). The predictor variables in this study were the type of archwire, type of dental arch and the time intervals. The outcome variable was the Irregularity Index score. The Irregularity Index was measured using 3D digital study models (e-models) and GeoDigm software from the VPS impressions taken at T1, T2 and T3. The data was analyzed with both a Two and Three-way Analysis of Variance (p≤0.05) to identify differences in the alignment of the maxillary and mandibular teeth and to determine differences between the two archwires. The Two and Three way ANOVA showed that there was a statistically significant difference (p≤0.05) in the alignment capabilities between the maxilla and the mandible. However, there was no evidence of a statistically significant difference (p=0.301) between NiTi and Supercable archwires at any time interval.